The effects of different caloric restriction diets on anthropometric and cardiometabolic risk factors in overweight and obese females - Mraović, Tatjana M; Radaković, Sonja; Ristić Medić, Danijela Ristić Medić; Tepšić Ostojić, Vesna; Rađen, Slavica; Hajduković, Zoran; Čairović, Aleksandra; Miljanović, Gora (Vojnosanitetski pregled, 2018)
Background/Aim. Obesity is an established risk factor for numerous chronic diseases. The aim of this study was to investigate the effect of well-balanced different caloric restriction (CR) diets on anthropometric parameters and standard biochemical cardiovascular risk markers [lipid profile, glucose homeostasis and high sensitivity C-reactive protein (hs-CRP)] in overweight/obese females. Methods. Participants (age 20–40 years) were randomized into 3 different CR diet groups: the group I – restriction of 20% calories from baseline energy requirements, the group II – restriction of 50% calories from baseline energy requirements and the group III – alternating daily diets with 70%/30% restriction. The study lasted 42 weeks. Anthropometric parameters were measured at the start and after 4, 8, 20 and 42 weeks after dietary intervention beginning. Biochemical markers were determined at baseline and after 20 and 42 weeks from dietary restriction start. Results. Body weight, body mass index (BMI), waist circumference (WC) and body fat (in %), in the different CR diet groups significantly decreased after 42 weeks. Body weight was less 11 kg in the group I and 12 kg in the groups II and III. WC was reduced by 11 cm in the groups I and III and by 10 cm in the group II. Different CR diets had the same effects on body fat (a reduction of 15% of body fat). Total cholesterol decreased by 7% in the group I and by 8% in the group III. Low density lipoprotein (LDL) cholesterol decreased by 14% in the group I and by 13% in group III. There were no significant changes in total and LDL-cholesterol levels in the group II. The atherogenic index presented as trigliceride/high density lipoprotein (TG/HDL) ratio decreased by 0.22 in the group I, by 0.25 in the group II and by 0.32 in the group III. Various CR diets had the same effects on reducing the hs-CRP levels. Conclusion. Different CR diets with the same macronutrient content are equally effective in reducing body weight, WC and body fat, improve cardiometabolic risk factors and decrease level of pro-inflammatory hs-CRP in overweight/obese females.